PENGARUH METODE BERNYANYI TERHADAP KEMAMPUAN MEMBACA AWAL PADA ANAK USIA 5-6 TAHUN DI TK YAMASSA SURABAYA - Noviasari, Dina (LPPM Universitas Muhammadiyah Cirebon, 2023)
The ability to read is an important foundation in opening up opportunities for a child's future, because it is the first step in mastering knowledge and knowledge. Therefore, teaching reading, especially early reading, can be done at the Kindergarten (TK) level. Observations made at the Yamassa Kindergarten in Surabaya showed that group B children were less interested in learning to read and 6 out of 11 children still could not read. To be able to improve children's early reading skills, educators must pay attention to children's competencies and consider methods that children will like so that learning is effective, such as the singing method. The purpose of this study was to determine whether or not there was an influence of the singing method to improve early reading skills in children aged 5-6 years at Kindergarten Yamassa Surabaya. This study uses a quasi-experimental research type and uses a non-equivalent control group design which uses a pretest and posttest given to the experimental group and the control group. Data collection techniques in this study are observation, interviews, tests, and documentation. This study used the Mann Whitney U Test and the results showed that there was a significant effect of the singing method on early reading skills in children aged 5-6 years at Kindergarten Yamassa Surabaya.